Fuzzy algorithm for 3D coastal gemorphology mapping by DInSAR - Marghany, Maged; Hashim, Mazlan (2007)

(untitled)
This paper introduces a new approach for mapping coastal geomorphology by using intergeration between fuzzy algorithm and differentioal sysnthetic aperature radar interferometry (DInSAR). The basic concept of fuzzy algorithm was used to filter DInSAR data. The equation of phase difference was modified by involving the weighted least square method. Then fuzzy B-spline algorithm for 3D object reconstruction was modified based on the phase equation modified by weighted least square method to ensure 3 D coastal geomorphology reconstruction. The real 3D coastal geomorphology elevation have been collected along the shoreline of Kuala Terengganu Malaysia. The study shows the DInSAR provides information about coastal geomorphology change with accuracy of Â± 0.2 m. It can be concluded that the integration between DInSAR and fuzzy B-spline can provide accurate map of 3D coastal geomorphology construction from historical RADARSAT-1 SAR fine mode data.